Investing in innovative food systems solutions in challenging contexts - World Food Programme; African Development Bank; International Food Policy Research Institute (International Food Policy Research Institute, 2025)
Humanitarian agencies are in a race against time to save lives in contexts where economies have collapsed as hunger is aggravated by conflicts and extreme weather, among other factors. Take Nigeria, for example. Across the country lives and livelihoods are being shattered by conflict and climate shocks – once a breadbasket, the northern regions now rely heavily on humanitarian food assistance. The numbers speak for themselves: 30.6 million people are food insecure – 10 million people in three northern states; 17 million children are malnourished – the highest number in Africa, second highest globally after India. Farmers are cut off from their fields. Traders struggle to move goods through dangerous or impassable roads. Millions are displaced. And yet amid this fragility pockets of resilience are emerging in areas where conflict has subsided such that some farmers can return to their farms.